Data cache prefetching design space exploration for BlueGene/L supercomputer - Brunheroto, J. R.; Salapura, V.; Redigolo, F. F.; Hoenicke, D.; Gara, A. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2005)
Scientific applications exhibit good spatial and temporal data memory access locality. It is possible to hide memory latency for the level 3 cache, and reduce contention between multiple cores sharing a single level 3 cache, by using a prefetch cache to identify data streams which can be profitably prefetched, and decouple the cache line size mismatch between L3 cache and the level 1 data cache. In this work, a design space exploration is presented, which helped shape the design of the BlueGene/L supercomputer memory sub-system. The prefetch cache consists of a small number of 128 line buffers that speculatively prefetches data from the L3 cache, since applications present some sequential access pattern, this prefetching scheme increases the likelihood that a request from the level 1 data cache was present in the prefetch cache. Since most compute intensive applications contain a small number of data streams, it is sufficient for the prefetch cache to have small number of line buffers to track and detect the data streams. This paper focuses on the evaluation of stream detection mechanisms and the influence of varying the replacement policies for stream prefetch caches.